Wybrane strategie rozpiętościowe wykorzystujące opcje na akcje - Majewska, Agnieszka (Using stock options in spread strategies, 2006)
The main goal of this article is to show how investor can use stock options quoted on the Warsaw Stock Exchange in spread strategies. Spread strategies are one of the most popular strategies in the market. Options spreads are simply the combination of two or more options. Bull call spread and bull put spread have been analysed in the article. Theoretical profits have been estimated for KGHM stock options.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 313-320